2016
DOI: 10.1038/nmat4804
|View full text |Cite
|
Sign up to set email alerts
|

Entropic contributions enhance polarity compensation for CeO2(100) surfaces

Abstract: Surface structure controls the physical and chemical response of materials. Surface polar terminations are appealing because of their unusual properties but they are intrinsically unstable. Several mechanisms, namely metallization, adsorption, and ordered reconstructions, can remove thermodynamic penalties rendering polar surfaces partially stable. Here, for CeO(100), we report a complementary stabilization mechanism based on surface disorder that has been unravelled through theoretical simulations that: accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 60 publications
(57 reference statements)
2
99
0
Order By: Relevance
“…Capdevila-Cortada et al showed that surface disorder created by partial removal of O could kinetically stabilise the bare (100) surface through fast surface diffusion process among nearly degenerate VO configurations. [46]. Judging from the positive value of the VO formation energy on fully water covered (100) surface, we infer that full water coverage can also provide a stabilisation mechanism for CeO2 (100) surface.…”
Section: Discussionmentioning
confidence: 74%
“…Capdevila-Cortada et al showed that surface disorder created by partial removal of O could kinetically stabilise the bare (100) surface through fast surface diffusion process among nearly degenerate VO configurations. [46]. Judging from the positive value of the VO formation energy on fully water covered (100) surface, we infer that full water coverage can also provide a stabilisation mechanism for CeO2 (100) surface.…”
Section: Discussionmentioning
confidence: 74%
“…For the (100) surface, half of the topmost oxygens were moved from the surface top layer to the bottom layer in order to reduce the polarity and render the system stoichiometric. Starting from this trench-like structure, two other low-energy reconstructions were investigated 33 . Each of these reconstructions allows for a different coordination shell around single-atom Pt.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we focus on these slabs as models for local, nanostructured regions (for example, step or edge sites) 24 . The low coordination of the surface oxygen atoms on the oxygen-terminated version increases their mobility 33 . As such, (100) restructures into various coexisting patterns at elevated temperatures encountered during pretreatment.…”
mentioning
confidence: 99%
“…This method has been used extensively in the case of ceria to describe its 4f states. [94][95][96] Although one can choose the on-site Hubbard interaction self-consistently, 97,98 it is usually chosen to fit to a given property, and that makes the method less robust and generalizable. Despite the fact that there are methods that have been developed to improve the robustness of calculation for periodic systems, including Green's function for periodic systems, 99 wave function in DFT embedding scheme for periodic systems, 100,101 hybrid functionals based on screened Coulomb potential, [102][103][104] and periodic coupled cluster, [105][106][107] there is still a need of reliable and affordable method for surface-deposited nanoclusters.…”
Section: Notes On the Computational Methodsmentioning
confidence: 99%